DAMPAK TATA KELOLA PERUSAHAAN DAN KUALITAS AUDIT TERHADAP PENGUNGKAPAN COVID-19 DI INDONESIA TAHUN 2020-2021 - Rasyid, Ganapati; Cahyonowati, Nur (Jurnal Akuntansi, 2024)
The purpose of this study is to examine the effect of corporate governance and audit quality on COVID-19 disclosure. The dependent variable used in this study is COVID-19 disclosure, while the independent variable used in this study consists of board size, board independence, board diversity, audit committee size, audit committee independence, audit office size, and audit opinion type. The population in this study consists of all companies registered in the Indonesian Stock Exchange during the years 2020-2021. The sampling method used is purposive sampling. The total number of samples in this study is 1,116 companies. Data analysis was performed by the descriptive statistic analysis and hypothesis test with multiple linear regression analysis. The result of this study shows that board independence and audit committee size have significantly positive effect on COVID-19 related information disclosure. Whereas board size, board diversity, audit committee independence, audit office size, and audit opinion type do not affect COVID-19 related information disclosure.